Common Property in the Perspective of Marriage Law in Indonesia - Isye Junita Melo,; Feibe Engeline Pijoh,; Novita Marven Mongdong,; Roof Pajow, (Technium Social Sciences Journal, 2024)
Common property is the property acquired throughout the marriage, from marriage entered into to marriage termination or divorce, death, or court decision. The settlement of the common property is often complicated and sometimes difficult to solve. This is because each side argues that they are the most contributing to the acquisition of the common wealth among the others. The results of the study show that if there is an agreement in the marriage then the property and common property of both parties will have a permanent legal certainty if viewed from a legal perspective. The settlement of common wealth is usually done by separation of the property of the two parties. The settlement of matters relating to the separation of joint property through the court may also be proposed through the submission of a claim by the party in the dispute or mediator through a lawyer. And an application for separation of property cannot be filed at the same time as a divorce claim.